Metagenomic analysis of primary colorectal carcinomas and their metastases identifies potential microbial risk factors - Marongiu, Luigi; Landry, Jonathan J. M.; Rausch, Tobias; Abba, Mohammed L.; Delecluse, Susanne; Delecluse, Henri-Jacques; Allgayer, Heike (Molecular oncology, 2021)
The paucity of microbiome studies at intestinal tissues has contributed to a yet limited understanding of potential viral and bacterial cofactors of colorectal cancer (CRC) carcinogenesis or progression. We analysed whole-genome sequences of CRC primary tumours, their corresponding metastases and matched normal tissue for sequences of viral, phage and bacterial species. Bacteriome analysis showed Fusobacterium nucleatum, Streptococcus sanguinis, F. Hwasookii, Anaerococcus mediterraneensis and further species enriched in primary CRCs. The primary CRC of one patient was enriched for F. alocis, S. anginosus, Parvimonas micra and Gemella sp. 948. Enrichment of Escherichia coli strains IAI1, SE11, K-12 and M8 was observed in metastases together with coliphages enterobacteria phage φ80 and Escherichia phage VT2φ_272. Virome analysis showed that phages were the most preponderant viral species (46%), the main families being Myoviridae, Siphoviridae and Podoviridae. Primary CRCs were enriched for bacteriophages, showing five phages (Enterobacteria, Bacillus, Proteus, Streptococcus phages) together with their pathogenic hosts in contrast to normal tissues. The most frequently detected, and Blast-confirmed, viruses included human endogenous retrovirus K113, human herpesviruses 7 and 6B, Megavirus chilensis, cytomegalovirus (CMV) and Epstein-Barr virus (EBV), with one patient showing EBV enrichment in primary tumour and metastases. EBV was PCR-validated in 80 pairs of CRC primary tumour and their corresponding normal tissues; in 21 of these pairs (26.3%), it was detectable in primary tumours only. The number of viral species was increased and bacterial species decreased in CRCs compared with normal tissues, and we could discriminate primary CRCs from metastases and normal tissues by applying the Hutcheson t-test on the Shannon indices based on viral and bacterial species. Taken together, our results descriptively support hypotheses on microorganisms as potential (co)risk factors of CRC and extend putative suggestions on critical microbiome species in CRC metastasis.
Gesehen am 28.11.2022